AI dan Masa Depan : Tantangan Etika Generasi Z - Syifa Chairunnisa; Fadhilla Amaniar (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
Advances in artificial intelligence (AI) technology have had a significant impact on people's lives, including Generation Z, in facing ethical challenges regarding the use of AI. This research uses a qualitative approach with a literature study method. Data was collected through a review of scientific journals, reference books and related research relevant to the topic. The research results show that Generation Z needs to improve digital skills and media literacy to face these challenges, especially in managing personal data privacy, understanding algorithm bias, and verifying information in cyberspace. This research suggests the importance of media literacy education and technical skills such as programming and cybersecurity as solutions to reduce the negative impact of AI technology on Generation Z.